Analysis of Contribution Samsat Pinang Sori Establishment on Motor Vehicle Tax Revenue in UPPD Samsat Pandan - Sri Dewi Rahayu Jamack; Erlina Erlina; Tarmizi Tarmizi (Budapest International Research and Critics University, 2021)
This study aims to analyze (1) the increase in the average realization of Motor Vehicle Tax at SAMSAT Gerai Pinang Sori on Motor Vehicle Tax Revenue at UPPD SAMSAT Pandan. (2) contribution of Motor Vehicle Tax at SAMSAT Gerai Pinang Sori to Motor Vehicle Tax Revenue at UPPD SAMSAT Pandan. (3) the effectiveness of the contribution of Motor Vehicle Tax at the SAMSAT Gerai Pinang Sori to the Motor Vehicle Tax Revenue at the UPPD SAMSAT Pandan. (4) Policies that can be applied to increase the Motor Vehicle Tax at SAMSAT Gerai Pinang Sori. (5) Is Motor Vehicle Tax Revenue (PKB) related to the regional development of Central Tapanuli Regency, North Sumatra Province. This research uses quantitative descriptive analysis method. The results showed that: (1) The average increase in the realization of the Motor Vehicle Tax (PKB) SAMSAT Gerai Pinang Sori for the last three years was 42.28%. (2) The contribution of Motor Vehicle Tax (PKB) SAMSAT Gerai Pinang Sori to the UPPD SAMSAT Pandan for the 2017 fiscal year was 3.9%, an increase in 2018 of 0.67 points to 4.57%. (3) The effectiveness of the contribution of the Motor Vehicle Tax (PKB) of SAMSAT Gerai Pinang Sori to the Motor Vehicle Tax (PKB) of UPPD SAMSAT Pandan is very less effective because it is only able to contribute below 10%. (4) SAMSAT Gerai Pinang Sori has done several things including socializing the latest policies regarding tax payments to the public, collecting taxes on motorized vehicles that are still in arrears or have not re-registered, especially motorized vehicles that have tax potential. large amount, the granting of relief from fines to taxpayers who are in arrears and the elimination of administrative sanctions. (5) Motor Vehicle Tax is related to regional development. Motor vehicle tax revenues are able to contribute to increasing PAD. From this PAD, it will be used or budgeted for infrastructure development in the region or in the province.